The Role of the County‐Elected Official in Disaster Recovery. Issue 3 (18th January 2016) - Bundy, Sarah J.; Jensen, Jessica
Abstract : Disaster recovery literature suggests that local governments are primarily responsible for the disaster recovery process within their communities. This literature also implies that part of this local government responsibility includes coordinating the different parts of the distributed function. Yet, it remains unknown how this responsibility for recovery—including coordination—is distributed within and across local government. This study explored the role of county‐elected officials in disaster recovery in an attempt to understand what role these elected officials currently play in the recovery process—particularly as related to the coordination of recovery efforts. Data were collected through 20 in‐depth, telephonic interviews with county‐elected officials in 12 states. Grounded theory was used to conceptualize the overall research design and analyze the data. The data showed that the role of the county‐elected officials could best be characterized as an extension of their routine role within the county government with no coordination function evident. Possible explanations of this finding related to role are offered and the implications of this finding for disaster recovery policy, practice, and scholarship are discussed.